Comparison of the influence of 2D and 3D geometry of the main chamber on plasma parameters in the SOL of ASDEX Upgrade. (23rd December 2021) - Bock, L.; Brida, D.; Faitsch, M.; Schmid, K.; Lunt, T.; the ASDEX Upgrade Team,
Abstract: In this paper the influence of toroidally asymmetric wall features on plasma solutions for ASDEX Upgrade is investigated by using the 3D scrape-off-layer simulation code EMC3-EIRENE. A comparison of simulation results in a 2D case with a toroidally symmetric first wall and divertor and a 3D case that differs from the 2D setup by including the 3D structure of the poloidal rib-limiters on the low field side of ASDEX Upgrade, highlights notable differences in the main chamber neutral particle distributions, ionisation sources and plasma flow patterns. Both neutral particle distribution and ionisation sources extend poloidally further upwards at the outer mid-plane in the 3D case and the plasma flow is globally influenced by the 3D wall features. Both simulations are conducted with identical input parameters to isolate the influence of wall geometry from other factors. By analysing the transport of neutrals from different poloidal locations it was possible to explain the observed discrepancies by different transport paths for recycled neutrals from the divertor region, only accessible in the 3D version of the wall geometry. Together with observed differences in fall-off lengths for plasma flow and electron temperature at the outer mid-plane, presented results are of key importance for interpreting global impurity migration experiments.